Implementación de cobro por el uso del vehículo y motocicleta como incentivo para la movilidad sostenible en Bogotá D.C. (2022)
Eng: In Bogotá city the vehicle has established like the king of mobility, becoming an element of social status, the motorcycle for has grown rapidly in the last two decades, together they account for 20% of trips generating externalities that are not compensated to society. With this scenery, a contribution should be implemented with an extra-fiscal function by reducing or changing adverse social behaviors such as the intensive use of vehicles and motorcycles in urban spaces. Through virtual surveys it was possible to know the socioeconomic profile of the users of these means of transport, as well as their provision to pay. The econometric analysis of the primary information indicates that the contribution corresponds to a rate of 7% of the reference value of the sale to the public of extra or regular gasoline per gallon. The collection would be made through the automotive service stations according to the number of gallons of fuel sold to the end customer, these resources will promote sustainable mobility through projects that benefit pedestrians, cyclists and users of public transport.